The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.inorgchem.2c03219
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Near-Infrared Luminescent 48-Metal Rectangular Zn(II)–Yb(III) Nanocluster with Carbonate Templates for the Dual-Emissive Detection of Rutin as a Medicinal Ingredient

Abstract: An interesting 48-metal Zn(II)–Yb(III) nanocluster (1) with a size of about 1.3 × 2.8 × 3.1 nm was constructed by carbonate templates from a Schiff base ligand. It exhibits ligand-centered emission and near-infrared (NIR) luminescence of Yb(III), which are used in the dual-emissive detection of rutin (Rut) with high sensitivity even in the presence of other interferences. The response behavior can be expressed by the second-order equation I 980 nm/I 510 nm = A*[Rut]2 + B*[Rut] + C, and the limits of detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…14 Recently, Peng et al reported a series of visible luminescent Ln-MOF-based (Ln = Eu or Tb) sensors for the detection of ingredients of natural medicines including Rut, 15 and we used a NIR luminescent Zn(II)−Yb(III) complex was used as sensor to detect the analyte. 16 High-nuclearity d-4f clusters may display unique molecular structures and good luminescence properties. 17,18 Schiff base ligands have been widely employed in the synthesis of NIR luminescent d-4f compounds; 19−21 for example, the d-block metal ions are Cd 2+ , 22 Zn 2+ , 23 Cr 2+ , 24 Ru 2+ , 25 and Pt 2+ .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Recently, Peng et al reported a series of visible luminescent Ln-MOF-based (Ln = Eu or Tb) sensors for the detection of ingredients of natural medicines including Rut, 15 and we used a NIR luminescent Zn(II)−Yb(III) complex was used as sensor to detect the analyte. 16 High-nuclearity d-4f clusters may display unique molecular structures and good luminescence properties. 17,18 Schiff base ligands have been widely employed in the synthesis of NIR luminescent d-4f compounds; 19−21 for example, the d-block metal ions are Cd 2+ , 22 Zn 2+ , 23 Cr 2+ , 24 Ru 2+ , 25 and Pt 2+ .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Some analysis techniques [e.g., ultraviolet–visible (UV–vis) spectrophotometry, high-performance liquid chromatography, electrochemical techniques, and capillary electrophoresis] have been employed in the determination of Rut concentrations. Some copper nanoclusters have been applied as fluorescence chemosensors to detect Rut. , Lanthanide complexes can demonstrate unique visible and near-infrared (NIR) emissions, for instance, narrow emission bands and long decay times . Recently, Peng et al reported a series of visible luminescent Ln-MOF-based (Ln = Eu or Tb) sensors for the detection of ingredients of natural medicines including Rut, and we used a NIR luminescent Zn­(II)–Yb­(III) complex was used as sensor to detect the analyte …”
Section: Introductionmentioning
confidence: 99%
“…Near-IR (NIR)-luminescent lanthanide complexes with Nd­(III), Er­(III), and Yb­(III) ions may show an advantage in the study of a biological system. , Schiff bases have been widely used to construct NIR-luminescent lanthanide complexes. Herein, we report the design and sensing properties of a NIR-luminescent Yb­(III) complex, [Yb 8 L 4 (DMF) 4 (EtOH) 4 ] ( 1 ; DMF = N , N -dimethylformiamide and EtOH = ethanol), with a new dodecadentate Schiff base ligand formed by the coupling of two Schiff bases (H 6 L; Scheme b). Interestingly, 1 exhibits luminescence response properties different from those of AE under excitation at two wavelengths (395 and 500 nm).…”
mentioning
confidence: 99%